Variación estacional de la composición mineral en pastizales de dehesa - GARCÍA CIUDAD, A.; MORENO DOMÍNGUEZ, A.; GARCÍA CRIADO, B. (Pastos, 1981)
The seasonal variations in the concentrations of sahes, N, P, K, Ca, Mg, Na, Fe, Mn, Cu and Zn in the pasture lands of a dehesas in the Pro- vince of Salamanca are studied. The sampling was monthly and took place during the period from September 1978 to October 1979. In general, the contení of ashes, N, P and K evolves in a similar ma- nner, reaching highest valúes in spring and lowest valúes in summer. Ho- wever, the concentrations of Ca, Mg and Mn show sharp oscilations at zone or fasture-type level. Those of Na, Cu and Zn are totally different from eteach other, but while in the Na concentration there are scarce fluc- tuations throughout the seasons, there are marked variations in the other tvvo. The elements Mg and Na are outstanding due to their relatively low concentrations which lie between 0 03 and 0.15% and 0.02 and 0.14% for the former and the latter, respectively. In the pasture land of the dehesa studied, it is usual to find deficien- cies in the elements Na, Cu and Zn throughout the year, while it is only in spring that the concentrations of N, P, Ca and Mg rise above the cri- tical levéis of an adequate nutrition for rumiants.
Keywords: composición mineral; Dehesa; pastizales; variación estacional (voyant)